Integrating Local Food into Early Childhood Nutritional Caregiving Practices among Working Parents: A Case Study of the Real Food Program - Riska Maratus Sholikah; Firda Ashlikhatul Kirom; Rachma Hasibuan; Ruqoyyah Fitri (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: Nutritional caregiving among working-parent families is increasingly influenced by dependence on ultra-processed foods (UPFs), driven by time limitations, convenience-oriented lifestyles, and changing family routines. Previous studies have mainly discussed local food within cultural preservation and nutrition education contexts, while limited research has examined its role as a practical feeding strategy for working families in early childhood education settings. Aims and scope of paper: This study aimed to examine the implementation of the Real Food Program as a local food-based integrative approach to strengthening nutritional caregiving practices among working-parent families in an early childhood education setting. Methods: This study employed a qualitative approach using an instrumental case study design conducted at KB Cahaya Tazkia Surabaya, Indonesia. Participants consisted of 30 working parents with children aged 3–6 years enrolled in the program. Data were collected through classroom and lunchbox observations, semi-structured interviews, and food photography documentation during program implementation. The data were analyzed using reflexive thematic analysis to identify patterns of parental feeding practices, food choices, and behavioral changes related to children’s nutrition. Results: The findings revealed that prior to the implementation of the program, children’s lunchboxes were largely dominated by ultra-processed foods selected for practicality and time efficiency, resulting in limited dietary diversity and inadequate nutritional balance. The Real Food Program encouraged significant changes in parental feeding practices through the increased inclusion of local foods, including traditional snacks and root crops (polo pendem), alongside improved food variety and nutritional quality. The program also fostered behavioral changes among working parents, including more intentional meal planning, reduced dependence on instant foods, and greater awareness of balanced nutrition within modern family lifestyles. Furthermore, the integration of local food strengthened children’s familiarity with culturally rooted food practices while promoting healthier eating behaviors. Contribution: This study proposes a contextual local food-based feeding ecology model that explains how family routines, parental feeding practices, school initiatives, and local food integration interact in shaping healthier eating behaviors among young children.